1973
DOI: 10.1136/bjo.57.11.849
|View full text |Cite
|
Sign up to set email alerts
|

Virus aetiology of certain cases of lacrimal obstruction.

Abstract: The aetiology of most cases of lacrimation due to stenosis or obstruction of the upper lacrimal drainage system is not yet known, but in some cases it is due to infection of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…25 Another possible mechanism is that an infl ammatory membrane caused by an adenovirus may produce adhesions between opposing raw surfaces of the lacrimal outlet system. 15,17,24 In particular, in infections with type 8 adenovirus, which is the major etiologic agent of EKC in East Asia, membrane formation has been well documented. 26,27 Histopathologic studies of membranes in EKC have revealed many polymorphonuclear leukocytes and some mononuclear infl ammatory cells entrapped in coagulated exudates.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…25 Another possible mechanism is that an infl ammatory membrane caused by an adenovirus may produce adhesions between opposing raw surfaces of the lacrimal outlet system. 15,17,24 In particular, in infections with type 8 adenovirus, which is the major etiologic agent of EKC in East Asia, membrane formation has been well documented. 26,27 Histopathologic studies of membranes in EKC have revealed many polymorphonuclear leukocytes and some mononuclear infl ammatory cells entrapped in coagulated exudates.…”
Section: Discussionmentioning
confidence: 98%
“…In infectious viral cases, the infl ammation extends beyond the mucosal epithelium into the deeper elastic layer, whereas in cases caused by microbes, it never extends into the elastic layer, and no stenosis of the lacrimal apparatus is observed. 15,17,24 In addition, narrow drainage structures such as the canaliculi are vulnerable to obstruction because of their mucosal wall proximity if they become infl amed. 25 Another possible mechanism is that an infl ammatory membrane caused by an adenovirus may produce adhesions between opposing raw surfaces of the lacrimal outlet system.…”
Section: Discussionmentioning
confidence: 99%
“…2 Eyelid nodules are present in 3% of the patients with chronic sarcoid. 3 The most common manifestations are small papules, 1 though papular eruptions, larger nodules, lupus pernio, ulcerated nodules, and plaques and swollen eyelids have been reported. 2 The ocular and adnexal involvement is more easily recognised in a patient with known sarcoidosis.…”
Section: Case Reportmentioning
confidence: 99%
“…Metastatic breast, lung, and prostate carcinoma account for most of the orbital metastases. [1][2][3][4][5][6][7] To our knowledge, orbital metastasis from carcinoma of the cervix has not been described before. We report a 46-year-old Chinese woman in whom orbital metastasis developed 4 months after she was diagnosed to have squamous carcinoma of the cervix.…”
Section: Orbital Metastasis From Carcinoma Of Cervixmentioning
confidence: 99%
“…9 Herpes zoster is also associated with canalicular obstruction, as is the vaccination for chicken pox. 10 Chlamydial infections have also been associated with canalicular obstruction in endemic areas. Lacrimal Obstruction…”
Section: Infective Causes (30%)mentioning
confidence: 99%